The Relationship between Personality Traits and Sport Injuries in Elite Wrestlers in Iran - Amirhossein Barati; Farshid Tahmasbi; Karim Biglar (University of Tehran, 2016)
The aim of the present study was to investigate the relationship between personality traits and incidence of injury in Iranian elite wrestlers. 60Iranian elite athletes participated in this study. Data were collected with injury report form and NEO personality questionnaire. The descriptive statistics and Pearson correlation coefficient at a significance level of 95% were used for data analysis.Results showed that all of the wrestlers suffered from at least two injuries during one season. The results showed a significant relationshipbetween personality traits includingneuroticism (P≤0.005), extraversion (P≤0.003), openness to experience (P≤0.047), agreeableness (P≤0.0001) and conscientiousness (P≤0.0001).Overall, findings indicated that personality traits such as low neuroticism, high extraversion, low openness to experience, high agreeableness and highconscientiousness helped elite athletes to better handle stressful situations in sports andto confront harmful psychological factors such as stress and anxiety through enhancing self-confidence and finally decrease injury incidence. Thus, officials, coaches, physicians and sport psychologists are recommended to plan to evaluate elite athletes' personality traits so that injury incidence can reduce and be prevented through a selection of those athletes with suitable personality traits.